CROWDFUNDING MODEL IN INDONESIA BASED ON PROFIT SHARING PRINCIPLE WITH BLUE OCEAN STRATEGY - Utami, Christina Whidya; Bramantyo, Paskalis Dio; Sumaji, Yoseva Maria (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The urgency of this research is that many SMEs in Indonesia face the constraint of limited access to capital and show a solution to overcome the problem of funding sources to finance SMEs by proposing a financing model through a crowdsourcing or crowdfunding mechanism . The crowdfunding model in this study is lending ( peer-to-peer) using the principle of profit sharing such as mudharabah which has not been widely studied. objective of this research is to analyze whether increasing financial inclusion of SMEs through crowdfunding based on the principle of profit sharing is the right model in improving the financial aspects of SMEs in Indonesia. The second year objective is: through the ERRC ( Blue Ocean Strategy ) approach , which factors should be eliminated ( Eliminate), Reduce , Raise and Create ( ERRC ) The aim of the research in the third year is to analyze the model for increasing financial inclusion of SMEs through crowdfunding based on the principle of profit sharing with the Business Model Canvas approach . The results of this study are based on the analysis of IFAS and EFAS shows the need for development at the internal level for crowdfunding improvement , compared to its external factors. Thus internal stakeholders such as local governments, managers become important actors for the process of strengthening profit-sharing crowdfunding .